Menyikapi Isu Kesetaraan Gender di Indonesia dalam Perspektif Imago Dei - Absalom, Lerry Kristian; Kaka, Bernardus; Tanhidy, Jamin (Jurnal Kala Nea, 2022)
The issue of gender equality is an issue that occurs in society. In certain societies gender discrimination does not seem to be a problem, even though it actually causes problems. Through this research, researchers examine the issue of gender equality in Indonesia. A theological research approach was used to address the issue of gender equality. The researcher found that the image of God in Genesis 1:26-28 is blurred by cultural factors. The image of God is to declare that human beings are the existence that reveals the form of God. Therefore, the presence of humans as the image of God implies that humans are the image of God who also inherits the attributes of God. Thus, men and women are in the image and likeness of God. Therefore, acts of gender discrimination are not feasible. Humans should not ignore each other as a perfect unity in God's creation. This is because God made men and women in His image and likeness.